DATA ANONYMIZATION AND CYBERSECURITY IN HEALTHCARE: A HESITANT LAW? - BERNELIN, Margo (MEDECINE LEGALE DROIT MEDICAL, 2025)
Researches in the field of cybersecurity demonstrate that anonymization technics are key to protecting confidentiality in health data and thus privacy. The law partly reflects this enthusiasm for data anonymization but also concedes that it is not infallible. This article aims not only to describe this hesitation on the part of the law, but also to question the reasons behind it.